2001
DOI: 10.1080/00222890109601916
|View full text |Cite
|
Sign up to set email alerts
|

Visual Information and the Control of Reaching in Children: A Comparison Between Children With and Without Developmental Coordination Disorder

Abstract: Three experiments were performed on reach and grasp in 9- to 10-year-old children (8 controls and 8 with developmental coordination disorder [DCD]). In normal reaching, children in the DCD group were less responsive to the accuracy demands of the task in controlling the transport component of prehension and spent less time in the deceleration phase of hand transport. When vision was removed as movement began, children in the control group spent more time decelerating and reached peak aperture earlier. Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 32 publications
5
29
2
1
Order By: Relevance
“…Especially, children with autism as well as controls showed longer MT, smaller PV, smaller PTPV, larger NJS, and smaller PTMGA in non-visual feedback and small target blocks. Thus, these findings were consistent with previous studies (Jakobson and Goodale 1991;Kuhtz-Buschbeck et al 1998a, b;Smyth et al 2001). Also, in the absence of visual information and higher task-accuracy, both groups needed longer executing time and longer correctional phrase.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Especially, children with autism as well as controls showed longer MT, smaller PV, smaller PTPV, larger NJS, and smaller PTMGA in non-visual feedback and small target blocks. Thus, these findings were consistent with previous studies (Jakobson and Goodale 1991;Kuhtz-Buschbeck et al 1998a, b;Smyth et al 2001). Also, in the absence of visual information and higher task-accuracy, both groups needed longer executing time and longer correctional phrase.…”
Section: Discussionsupporting
confidence: 94%
“…Time to MGA is the time from movement onset to MGA, and its percentage in MT is PTMGA (Kuhtz-Buschbeck et al 1998b). Therefore, Smyth et al (2001) on this note, stated that when the degree of task difficulty is higher, PTMGA would be smaller, which means MGA occurs earlier.…”
Section: Kinematic Variablesmentioning
confidence: 94%
“…We found a clear developmental trend in line with this hypothesis where younger children (aged 5-8 years) showed a greater bias towards selecting an MR grip than older children (aged 9-14 years). We had also hypothesised that a group of children with DCD would be biased towards MR at all ages due to their known prehension difficulties (Smyth, Anderson & Churchill 2001;Mon-Williams et al, 2005). The children with DCD showed the predicted bias towards MR, and the proportion of children with DCD who showed the MR bias was higher than even the youngest group of typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…Smyth, Peacock, and Katamba (2004) found that 5-and 6-year-old children did not spend more time in the low-velocity phase of movement when they could not see their hand and did not increase grip aperture, as 9-and 10-year-olds did and as adults have been shown to do. In addition, in a study of reach and grasp in 9and 10-year-old children with poor coordination, Smyth, Anderson, and Churchill (2001) found that these children showed less asymmetry in velocity profiles when reaching in normal light and that they were less affected by the removal of sight of the hand and the target than were agematched control children. Younger children, and children with poor coordination, do not respond to absence of sight of the hand by slowing the end of the movement, thus increasing the asymmetry in the velocity profile, or by increasing error margins in grip aperture.…”
mentioning
confidence: 96%